Finding Gene Regulatory Networks in Psoriasis: Application of a Tree-Based Machine Learning Approach - Deng, Jingwen; Schieler, Carlotta; Borghans, José A. M.; Lu, Chuanjian; Pandit, Aridaman (Frontiers in Immunology, 2022)
Psoriasis is a chronic inflammatory skin disorder. Although it has been studied extensively, the molecular mechanisms driving the disease remain unclear. In this study, we utilized a tree-based machine learning approach to explore the gene regulatory networks underlying psoriasis. We then validated the regulators and their networks in an independent cohort. We identified some key regulators of psoriasis, which are candidates to serve as potential drug targets and disease severity biomarkers. According to the gene regulatory network that we identified, we suggest that interferon signaling represents a key pathway of psoriatic inflammation.